1999
DOI: 10.1080/11250009909356230
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiaand the antifilarial properties of tetracycline. An untold story

Abstract: The idea that tetracycline may have antifilarial properties was first proposed in 1960. Data were subsequently published on the effects of tetracycline on the development and reproduction of Brugia pahangi in both the mosquito and mammalian hosts. These studies were apparently ignored until recently. In 1998, it was suggested that the antifilarial properties of tetracycline may derive from the presence of the bacterial endosymbiont Wolbachia in filarial worms. In view of this renewed interest, we would like to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 6 publications
0
22
0
4
Order By: Relevance
“…In this way, L. yutajensis could become a valid alternative to the use of A. viteae (which is negative for W. pipientis) as a sort of 'negative control' (e.g. see Hoerauf et al, 1999;McCall et al, 1999;Taylor et al, 2000 andSaint André et al, 2002), being more closely related to a filarial model which harbors W. pipientis (L. sigmodontis) than A. viteae (see Casiraghi et al, 2001b). Litomosoides species are thought to have evolved as parasites of bats in South America, and diversified in rodents only recently (about 3 millions years), when these migrated from North America during the Pliocene-Pleistocene; their passage into small marsupials is also believed to have occurred after the Pliocene-Pleistocene Philipp, 1991 andGuerrero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, L. yutajensis could become a valid alternative to the use of A. viteae (which is negative for W. pipientis) as a sort of 'negative control' (e.g. see Hoerauf et al, 1999;McCall et al, 1999;Taylor et al, 2000 andSaint André et al, 2002), being more closely related to a filarial model which harbors W. pipientis (L. sigmodontis) than A. viteae (see Casiraghi et al, 2001b). Litomosoides species are thought to have evolved as parasites of bats in South America, and diversified in rodents only recently (about 3 millions years), when these migrated from North America during the Pliocene-Pleistocene; their passage into small marsupials is also believed to have occurred after the Pliocene-Pleistocene Philipp, 1991 andGuerrero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In arthropods W. pipientis generally induces alterations in host reproduction (Werren, 1997;Stouthamer et al, 1999 andBandi et al, 2001). In filarial nematodes there is convincing evidence that these bacteria are required for the development and reproduction of their hosts Bandi et al, 1999;Hoerauf et al, 1999;McCall et al, 1999;Hoerauf et al, 2000 andCasiraghi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Various biological means of mange mite control are being explored including the use of entomopathogenic fungi Brooks and Wall 2001). In this context, the study of the internal bacterial flora of Psoroptes mites could also give useful information, because some recent studies on bacterial endo-symbionts of other mammalian parasites, such as those of filarial nematodes, have shown that bacteria of the genus Wolbachia are necessary for normal embryogenesis and are transmitted transovarially; this has led to the possibility of the use of tetracycline for the control of these parasites (Bosshardt et al 1993;Bandi et al 1999;McCall et al 1999).…”
Section: Introductionmentioning
confidence: 98%
“…This phylogenetic pattern suggests that ®larial nematodes and their Wolbachia share a long co-evolutionary history which should have led to reciprocal co-adaptation and dependence . Indeed, tetracycline treatments targeted towards Wolbachia are detrimental to those ®larial hosts harbouring Wolbachia (Bosshardt et al 1993;Genchi et al 1998;Hoerauf et al 1999;McCall et al 1999;Langworthy et al 2000). Intracellular bacteria have been observed, but not yet identi®ed, in the ®larial nematode Mansonella ozzardi (Kozek and Raccurt 1983), a parasite of the body cavity of humans in Latin America, from northern Argentina to the Yucatan peninsula and the West Indies.…”
Section: Introductionmentioning
confidence: 99%